Catheter Ablation of Ischemic Ventricular Tachycardia With Remote Magnetic Navigation: STOP‐VT Multicenter Trial. (March 2016) - SKODA, JAN; ARYA, ARASH; GARCIA, FERMIN; GERSTENFELD, EDWARD; MARCHLINSKI, FRANCIS; HINDRICKS, GERHARD; MILLER, JOHN; PETRU, JAN; SEDIVA, LUCIE; SHA, QUN; JANOTKA, MAREK; CHOVANEC, MILAN; et al.
Study to Obliterate Persistent Ventricular Tachycardia: Introduction: Catheter ablation is an effective treatment of scar‐related ventricular tachycardia (VT), but the overall complexity of the procedure has precluded its widespread use. Remote magnetic navigation (RMN) has been shown to facilitate cardiac mapping and ablation of VT in a retrospective series. STOP‐VT is the first multicenter, prospective, single‐arm and single‐procedure study evaluating RMN‐based mapping and ablation of post‐infarction VT. Methods: Patients with documented VT and prior MI, in whom an ICD was implanted either for primary or secondary prevention, were recruited from four EU and US centers. Either a transseptal (48 patients) or transaortic (5 patients) approach was employed to gain access for ventricular endocardial mapping/ablation during VT (entrainment mapping, activation mapping) and/or substrate mapping in sinus rhythm (elimination of fractionated/late potentials, variable extent of substrate modification) with RMN and irrigated RF ablation. The primary endpoints were as follows: (i) non‐inducibility of the target VT or any other sustained VT; (ii) elimination of sustained VT/VF during ICD follow‐up of up to 12 months. Results: The cohort included 53 consecutive patients (median age 67 years, 49 men, median LVEF 31%). One hemodynamically unstable patient was excluded at the onset of mapping. Inducibility of sustained VT was achieved an average of 2.2 times per patient (1–8), with mean tachycardia cycle length (TCL) 374 milliseconds (179–510). Mean total procedure and fluoroscopy times were 223 minutes and 8.7 minutes, respectively; mean cumulative fluoroscopy time during mapping and ablation was 0.95 minutes; maximum power averaged 42.3 W with nominal saline 30 cc/min irrigation; mean cumulative RF time was 38 minutes. Non‐inducibility of the target VT was achieved in 49/52 patients (94.2%) and non‐inducibility of any VT was achieved in 38/52 patients (73.1%). A combination of RMN and manual ablation was performed in two patients, rendering one non‐inducible. During the 12‐month ICD follow‐up period, freedom from any sustained VT/VF was observed in 30 patients (62%), of which 19 (63%) were off antiarrhythmic medications. Five patients expired during follow‐up: one presented with a VT storm, but for the others, death was not related to VT/VF (MI‐cardiogenic shock, pulmonary embolism, bronchogenic carcinoma, end stage heart failure). No procedural complications were reported. Conclusions: This first prospective, single‐procedure, multicenter study indicates that remote magnetic navigation is a safe and effective method for catheter ablation of post‐infarction VT.